2012
DOI: 10.1111/j.1443-1661.2012.01320.x
|View full text |Cite
|
Sign up to set email alerts
|

Carbon dioxide insufflation safety in double‐balloon enteroscopy: An experimental animal study

Abstract: The use of CO(2) for insufflation during DBE was safe and no complications associated with CO(2) were observed. In addition, the use of CO(2) offers benefits over the use of room air for insufflation during DBE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 23 publications
(48 reference statements)
0
6
0
Order By: Relevance
“…These findings were confirmed by Wang et al, but not for the DBE procedure [25]. This was especially interesting because all existing randomized controlled trials have favored CO 2 insufflation [16,17] and its benefit has also been confirmed in an animal experimental set-up [36]. When retracting the endoscope during the push-and-pull-procedure, loop-formation and trapped insufflation gas are considered to be responsible for discomfort and pain.…”
mentioning
confidence: 85%
“…These findings were confirmed by Wang et al, but not for the DBE procedure [25]. This was especially interesting because all existing randomized controlled trials have favored CO 2 insufflation [16,17] and its benefit has also been confirmed in an animal experimental set-up [36]. When retracting the endoscope during the push-and-pull-procedure, loop-formation and trapped insufflation gas are considered to be responsible for discomfort and pain.…”
mentioning
confidence: 85%
“…The use of an additional cannula system and CO 2 instead of indoor air has also shown to increase the technical achievement rate with DBE, and decompress air during the examination in order to make deep intubation [ 16 , 17 ]. New indications associated with DBE have begun to evolve in clinical practice.…”
Section: New Developmentsmentioning
confidence: 99%
“…Soria et al reported that CO 2 insufflation improved intubation depth during double-balloon enteroscopy in the experimental animal study. 16 This meta-analysis showed that CO 2 insufflation improves intubation depth for oral enteroscopy. It is worth noting that this meta-analysis also demonstrates heterogeneity of intubation depth for oral enteroscopy.…”
Section: Discussionmentioning
confidence: 96%